Elastase treatment of tendon specifically impacts the mechanical properties of the interfascicular matrix. (15th March 2021) - Godinho, Marta S.; Thorpe, Chavaunne T.; Greenwald, Steve E.; Screen, Hazel R.C.
Abstract: The tendon interfascicular matrix (IFM) binds tendon fascicles together. As a result of its low stiffness behaviour under small loads, it enables non-uniform loading and increased overall extensibility of tendon by facilitating fascicle sliding. This function is particularly important in energy storing tendons, with previous studies demonstrating enhanced extensibility, recovery and fatigue resistance in the IFM of energy storing compared to positional tendons. However, the compositional specialisations within the IFM that confer this behaviour remain to be elucidated. It is well established that the IFM is rich in elastin, therefore we sought to test the hypothesis that elastin depletion (following elastase treatment) will significantly impact IFM, but not fascicle, mechanical properties, reducing IFM resilience in all samples, but to a greater extent in younger tendons, which have a higher elastin content. Using a combination of quasi-static and fatigue testing, and optical imaging, we confirmed our hypothesis, demonstrating that elastin depletion resulted in significant decreases in IFM viscoelasticity, fatigue resistance and recoverability compared to untreated samples, with no significant changes to fascicle mechanics. Ageing had little effect on fascicle or IFM response to elastase treatment. This study offers a first insight into the functional importance of elastin in regional specific tendon mechanics. It highlights the important contribution of elastin to IFM mechanical properties, demonstrating that maintenance of a functional elastin network within the IFM is essential to maintain IFM and thus tendon integrity. Statement of significance: Developing effective treatments or preventative measures for musculoskeletal tissue injuries necessitates the understanding of healthy tissue function and mechanics. By establishing the contribution of specific proteins to tissue mechanical behaviour, key targets for therapeutics can be identified. Tendon injury is increasingly prevalent and c hronically debilitating, with no effective treatments available. Here, we investigate how elastin modulates tendon mechanical behaviour, using enzymatic digestion combined with local mechanical characterisation, and demonstrate for the first time that removing elastin from tendon affects the mechanical properties of the interfascicular matrix specifically, resulting in decreased recoverability and fatigue resistance. These findings provide a new level of insight into tendon hierarchical mechanics, important for directing development of novel therapeutics for tendon injury. Graphical abstract: Image, graphical abstract